Pengaruh Motivasi Kerja Guru Terhadap Kepuasan Kerja Guru Di SDN Tireman Rembang - Purnomo, Yulianto Hery; Dianti, Wahyu Rahma; Nurkolis, Nurkolis (Jayapangus Press, 2025)
This study aims to analyze the influence of work motivation on teacher job satisfaction at SDN Tireman Rembang. This research uses a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to 30 teachers at SDN Tireman, which measured the work motivation and job satisfaction variables using a Likert scale. The results of statistical analysis show that work motivation has a significant influence on teacher job satisfaction. The higher the work motivation of teachers, the higher the level of job satisfaction they experience. Both variables are positively related, both partially and simultaneously. The work motivation of teachers at SDN Tireman Rembang is in the high category, with an average score of 4.14, while teacher job satisfaction is also in the high category with an average score of 4.22. These findings indicate that the teachers at the school have high work enthusiasm and good job satisfaction in carrying out their duties as educators. Therefore, the school and policymakers need to continuously strive to maintain and improve teachers' work motivation, such as through rewards, professional development, improved facilities, and creating a harmonious work environment. In this way, teacher job satisfaction can be continuously improved, which will ultimately have a positive impact on the quality of education at the school.